Variabilitas Penggunaan Model Pembelajaran Pada Kegiatan Pembelajaran Sejarah Peminatan Kelas X IPS di Kota Depok - Yusuf Budi Prasetya Santosa; Fahmi Hidayat (LP4MK STKIP PGRI Lubuklinggau, 2020)
The use of varied learning models by history teachers will facilitate teachers and students in implementing and following the learning process. This study aims to determine the learning process and the use of learning models used by history teachers. This study uses a qualitative methodology with an observation and interview approach conducted at two high schools, Dian Didaktika High School and SMA Negeri 2 Depok. From the results of the study it can be seen, that the history teacher at the two schools has carried out the learning process using a scientific approach. There is no difference in the selection of learning strategies, both of them use the contextual teaching learning model. The difference between the two is in the selection of learning methods, where the history teacher Dian Didaktika uses the method of learning project base learning and the history teacher of SMA Negeri 2 Depok uses a method of learning outside the classroom by visiting museums.